2017
DOI: 10.12982/cmujns.2017.0025
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sources of PM10 Burning-Season Haze in Northern Thailand Using Nuclear Analytical Techniques

Abstract: This study explored the sources of PM 10 in the smoke haze during the traditional burning season in northern Thailand by determining the characteristics of the atomic elements in PM 10 compared to known plant samples. The ambient air was collected from two sites (urban and peri-urban) in the Chiang MaiLamphun Basin. This was compared to the characteristics of the leaves from eight agricultural and forest plants predominant in the region: bamboo, grass, teak, yangna, corn, longan, lychee, and rice that were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…The major direction of the air masses at both sites passed through southern Myanmar and the parts of Mae Hong Son. In this region, there was high distribution of fire hotspots during the study period as also shown in previously reports (Khamkaew et al, 2016;Kiatwattanacharoen et al, 2017;Punsompong and Chantara, 2019).…”
Section: Evidence From Hotspot Maps and Trajectorysupporting
confidence: 87%
See 1 more Smart Citation
“…The major direction of the air masses at both sites passed through southern Myanmar and the parts of Mae Hong Son. In this region, there was high distribution of fire hotspots during the study period as also shown in previously reports (Khamkaew et al, 2016;Kiatwattanacharoen et al, 2017;Punsompong and Chantara, 2019).…”
Section: Evidence From Hotspot Maps and Trajectorysupporting
confidence: 87%
“…Khamkaew et al, (2016) reported that the mean PM2.5 concentrations collected at Chiang Mai University (CMU) between March and April 2014 were largely attributed to local open burning of agricultural matter and forest fires (Khamkaew et al, 2016). Air pollution in Chiang Mai City studied in the dry season of 2010 suggested that open burning of plants was the predominant contributor to air pollution in this area and was found to be highly correlated with element concentrations in ambient PM10 (particulate matter with an aerodynamic diameter less than 10 µm) and the combustion of teak, yangna, and corn stalks (Kiatwattanacharoen et al, 2017). Mae Chaem (MC) is a rural district in Chiang Mai Province and the terrain consists of mostly foothills and mountain ridges surrounding a small basin approximately 350 m above mean sea level.…”
Section: Introductionmentioning
confidence: 99%
“…It makes substantial contributions of 29% and 16% of O 3 and CO, respectively, during the high-emission period in March compared to those in the low-emission period in December. As much as 70% of biomass burning in this region occurs in Myanmar and Laos, as reported by Punsompong and Chantara (2018) and Kiatwattanacharoen et al. (2017).…”
Section: Introductionsupporting
confidence: 67%
“…To better understand whether specific types of biomass have differential toxicity, PM samples could also be generated in the laboratory, by burning biomass samples that are relevant to Thailand (e.g. Bambusa vulgaris, Echinochloa crus-galli, Tectona grandis, Diptero carpusalatus, Zea mays, Oryza sativa, Dimocarpus longan, and Litchi chinensis [120]) and testing the toxicity of the emitted PM in vitro and in vivo.…”
Section: In Vivo Versus In Vitro Modelsmentioning
confidence: 99%